Seasonal and spatial variabilities of dissolved iron in southern Yellow Sea. (October 2020) - Zhu, Minghan; Yang, Rujun; Li, Yan; Su, Han; Shan, Qianqian; Ning, Yutong; Fu, Shulin; Wang, Shirong
Abstract: The southern Yellow Sea (SYS) is considered to be of the most prolific fishing grounds in the China Sea. In this study, the seasonal and spatial distributions of total dissolved iron (DFe) are investigated across four seasons in the SYS, from July 2013 to January 2016. This investigation showed that the DFe values of all samples exhibited seasonal variations: summer (1.7–15.8 nM), autumn (0.9–38.5 nM), winter (3.0–69.8 nM), and spring (3.0–100.2 nM). The DFe values in both surface and bottom waters also exhibited distinct temporal changes. The influence of water masses on the distribution of DFe as well as other factors, such as major nutrient concentrations of total dissolved nitrogen, total dissolved phosphate, and hydrologic factors, was investigated in this study. Based on the investigation of DFe and major nutrients in the SYS, the Yellow Sea Cold Water Mass was identified as the most conservable water mass in the study area. The results of this study further indicate that in winter, DFe0.4 μm (using a 0.4 μm filter) is considerably higher than DFe0.2 μm (using a 0.2 μm filter) in the surface water of the SYS coastal area. Therefore, the dissolution of colloidal Fe in this area had a significant effect on DFe. Highlights: Seasonal distributions of DFe are reported in the SYS, which has the most abundant fishery resources in China Sea. The blooms of green tides in Subei Shoal caused influence on the DFe concentration in summer. Based on the relationship between DFe and nutrients, the YSCW is the most conservative among the water masses in the SYS.